Genetic analysis of children with congenital ocular anomalies in three ecological regions of Nepal: a phase II of Nepal pediatric ocular diseases study - Srijana Adhikari; Neelam Thakur; Ujjowala Shrestha; Mohan K Shrestha; Murarai Manshrestha; Bijay Thapa; Manish Poudel; Ajaya Kunwar (BMC, 2020)
Abstract Background Genetic eye diseases constitute a large and heterogeneous group of childhood ocular morbidity. Individual diseases may cause multiple structural anomalies and developmental features. Nepal Pediatric Ocular Disease Study (NPODS) was a population-based epidemiological study conducted across three ecological regions of Nepal to determine the prevalence and etiology of childhood ocular morbidity and blindness. In Phase II of this study, genetic analysis was performed for children who were found to have congenital ocular anomalies. Method It was a cross sectional descriptive study. A total of 10,270 children across three different ecological regions in Nepal (Low lands, hills, and mountains) underwent ocular examinations in NPODS. Out of 374 (3.6%) of children with ocular abnormalities, 30 were thought to be congenital in nature. Targeted genetic analysis, including genotyping for genes specific to presenting phenotype, was performed for 25 children using serum samples. Results Out of 25 children, 18 had meaningful genetic results. Analysis revealed one missense alteration G12411T of Zinc Finger Homeobox 4 (ZFHX4) gene in one participant among 10 with congenital ptosis and another missense variation T > C P. Y374 C of Signaling Receptor and Transporter Retinol 6 (STRA6) gene in one participant among 3 with microphthalmos. Conclusion The study is first of its kind from Nepal and mutant genes were unique to Nepalese Population. Further analysis of genetic factors is crucial to better understand genetic association with ocular diseases and conditions. This helps further in genetic counseling and probably gene therapy to prevent blindness from these conditions.